The role of training devices in teacher professional development - Arnosti, Rebeca (2023)
The aim of this study was to analyze training devices and see what role they play in teachers’ professional development. We carried out a qualitative study with a constructive-collaborative approach through participant observation, focus groups and questionnaires involving 3 schools and 92 subjects. We identified and produced student monitoring devices and socio-professional monitoring devices. It turned out that the devices straddle the fine line between being bureaucratic and/or generating formative meanings. It proved to be important to (re)develop them collecti-vely and have socio-professional support from those coordinating the process. In successful situations, the devices have assisted the school’s organizational development.